Makna Ekonomi Berhaji Bagi Suku Banjar (Kajian Antropologi Budaya) - Amelia Rahmaniah; Rahmat Shodiqin (PT. Sharia Journal and Education Center, 2024)
Abstract Hajj, which is often assumed to be related to spirituality and considered part of the domain of religion, actually has an economic meaning as well. This economic meaning is one of the reasons for the high number of Hajj pilgrims in South Kalimantan, which is dominated by the Banjar tribe, which likes to go to Hajj many times. Existing research has shown that the meaning of Hajj differs from one person to another, so in the current study the meaning of Hajj is considered to be the personal meaning of the performer. This research will specifically show the economic meaning of Hajj for the Banjar tribe. The method used in this research is interviews with nine people from the Banjar tribe. The findings in this study show that Hajj can make sustenance abundant and blessed, Hajj will make business (work) smooth and blessed, and not performing Hajj results in the loss of wealth. Keywords: economic meaning, hajj, Banjar tribe Abstrak Haji yang sering diasumsikan berkaitan dengan spritual dan dianggap sebagai bagian dari domain religion sebenarnya haji juga mempunyai makna ekonomi. Makna ekonomi ini merupakan salah satu penyebab tingginya angka berangkat haji di Kalimantan Selatan yang didominasi oleh Suku Banjar yang gemar berkali-kali berangkat haji. Penelitian yang telah ada menunjukkan bahwa makna haji berbeda antara satu orang dengan yang lainnya sehingga dalam studi saat ini pengertian haji dianggap sebagai makna pribadi pelakunya. Penelitian ini secara khusus akan menunjukkan makna ekonomi haji bagi suku Banjar. Metode yang digunakan dalam penelitian ini adalah wawancara dengan sembilan orang dari suku Banjar. Temuan dalam penelitian ini menunjukkan bahwa haji dapat menjadikan rezeki berlimpah dan berkah, haji akan menjadikan usaha (pekerjaan) lancar dan berkah, dan tidak jadi melaksanakan haji berakibat habisnya harta. Kata Kunci: makna ekonomi, haji, suku Banjar